PROMOTING SCIENTIFIC LITERACY BY USING SCIENCE, TECHNOLOGY, SOCIETY, AND ENVIRONMENT (STSE) APPROACH OF GRADE 11 STUDENTS ON THE TOPIC OF PLANT GROWTH - Chanapimuk, Kultida; Sawangmek, Sureeporn; Nangngam, Pranee (Journal of Education and Innovation, 2020)
Nowadays, Scientific literacy is necessary for students to use scientific knowledge to consider and solve the problem for life in today’s world. One of the key issues is the using of agrochemical products that led to health problem, customer safety and environmental issues. This action research purposed to investigate how to use Science, Technology, Society, and Environment (STSE) approach to promote students’ scientific literacy of grade 11 students on topic of plant growth and to examine students’ scientific literacy after learning by the STSE approach. The data was collected from STSE learning activity plan, reflective learning tools, PISA-like test and student worksheets. The data was analyzed using content analysis, mean and percentage and examine using resource and method triangulation. The findings showed that STSE approach should start with environmental issues for motivation; exploration; brainstorming and decision making to choose the best way of the class. The students who learnt though STSE approach have higher scientific literacy. According to the high scores of the competencies of scientific literacy throughout the study. The most developed competency was interpreting data.